Demand model of international visitors to the Kilim Karst Geoforest Park, Langkawi : application of ITCM model - Matthew, Nitanan Koshy; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Education and Novel Technology Research Association, 2013)
Kilim Karst Geoforest Park in Langkawi offers rural tourism attractions to the visitors. The rural tourism demand model of international visitors to the site can be developed using the non-market valuation techniques. One of the common techniques is using the revealed preference technique, which is the Travel Cost Model (TCM). There have been various modifications made to the basic TCM developed by Clawson 1959. Modification of the basic TCM takes into account other factors that may shift the demand of visitors. The individual travel cost model (ITCM) has been employed in the research. Thus, the main objective of this article is to develop the rural tourism demand model for the park using the individual travel cost model (ITCM). In addition, the basic TCM model is estimated to determine the consumer surplus value of the international visitors to the park. Structured questionnaire and face-to-face data collection method are employed to obtain the primary data from 330 international visitors using the convenient sampling technique. Poisson regression analysis has been conducted to estimate the basic TCM model. The finding for ITCM shows that the consumer surplus value per trip for the Langkawi model €6993 is greater than for the Kilim models (€1437 and €633) for the Poisson regression analysis.